A gradient-guided spatiotemporal network for lithology identification in complex coal-bearing strata - Shuangcheng Yang; Xiaoying Lin; Zhonghao Zhang; Xiang Yu (Earth Science Informatics, 2026)

Data augmentation framework for rock thin section identification and classification under the condition of small samples - Chen Zhang; Kai Lin (Earth Science Informatics, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

A web-based intelligent computing application for critical elements in Chinese coals - Na Xu; Wenze Lin; Pengfei Li; Qingfeng Wang (Earth Science Informatics, 2026)

Dynamic snake vision mask r-cnn: a method for microfracture detection in electrical logging imaging - Yihang Lu; Sinan Fang; Yi Yu; Huimin Wu; Guilan Lin; Guohao Ma; Zehan Wang (Earth Science Informatics, 2025)

Spatiotemporal prediction of grassland net primary productivity using deep learning models integrating temporal decomposition and spatial clustering: a case study in source region of the Yellow River, China - Fujiang Liu; Tianqi Wu; Weihua Lin; Yan Guo (Earth Science Informatics, 2025)

Feasibility of a hybrid AHA-GPR model for predicting blasting fragmention in surface mines - Zhi Yu; Lin-Feng Du; Jian-Xing Liu; Jian Zhou; Chuan-Qi Li (Earth Science Informatics, 2025)

Deep multivariable spatial attention CNN-based spatial grid NWP error correction for accurate one-day-ahead photovoltaic power forecast - Mingliang Bai; Ruidong Wang; Chaojing Lin; Yunxiao Chen; Fuxiang Dong; Zhihao Zhou; Xusheng Yang; Jinfu Liu; Daren Yu (Earth Science Informatics, 2025)

Spatio-temporal response characteristics of flood embankment deformation during shield tunnel excavation - Qingxiong Zhao; Ping Cao; Jinshuo Liu; Hang Lin (Earth Science Informatics, 2025)

Metakaolin as a soil stabilizing admixture: A comprehensive analysis of California bearing ratio and consolidation behavior using experimental and machine learning approaches - Ibrahim Haruna Umar; Sale Abubakar; Hang Lin; Jubril Izge Hassan (Earth Science Informatics, 2025)

Mechanical properties and failure modes of discontinuous jointed considering water softening effects - Siyu Chen; Hang Lin; Ke Ou; Xing Zhang; Chaoyi Yang (Earth Science Informatics, 2025)

Study on frost deformation of rock and calculation method of frost heaving rate of tunnel surrounding rock in cold regions - Wenliang Qiu; Fengqi Shen; Jingyu Zhou; Lin Qi; Mingming Xing (Earth Science Informatics, 2025)

Short-term coalbed methane concentration prediction and early warning based on the STL-ENN-GRU hybrid model - Kangle Li; Lin Jiang; Yan Zhang; Mei Wang; Yuancheng Li; Kun Yang (Earth Science Informatics, 2025)

Upper limit analysis for seismic sliding stability of double-sided limited narrow slope retaining wall - Zeyue Wang; Hang Lin; Yanhui Cheng (Earth Science Informatics, 2025)

Risk assessment of water inrush in deep-buried karst tunnel with rich water based on combined weighting method - Xin Zhang; Yunda Lin; Zongyuan Pan; Xiaozhen Jiang (Earth Science Informatics, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

A method for landslide identification and detection in high-precision aerial imagery: progressive CBAM-U-net model - Hanjie Lin; Li Li; Yue Qiang; Xinlong Xu; Siyu Liang; Tao Chen; Wenjun Yang; Yi Zhang (Earth Science Informatics, 2024)

Exploring advanced machine learning techniques for landslide susceptibility mapping in Yanchuan County, China - Wei Chen; Chao Guo; Fanghao Lin; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2024)

Real-time sharing algorithm of earthquake early warning data of hydropower station based on deep learning - Gang Yang; Min Zeng; Xiaohong Lin; Songbai Li; Haoxiang Yang; Lingyan Shen (Earth Science Informatics, 2024)

A 3D bedrock modeling method based on information mining of 2D geological map - Tong Niu; Bingxian Lin; Liangchen Zhou; Guonian Lv (Earth Science Informatics, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

Soil respiration estimation in desertified mining areas based on UAV remote sensing and machine learning - Ying Liu; Jiaquan Lin; Hui Yue (Earth Science Informatics, 2023)

A general characterization of integrating and querying heterogeneous fuzzy spatiotemporal XML data - Lin Zhu; Jiahui Wang; Luyi Bai (Earth Science Informatics, 2023)

Lithology identification based on interpretability integration learning - Xiaochun Lin; Shitao Yin (Earth Science Informatics, 2023)

Exploring watershed structural variation during watershed evolution process under artificial rainfall experiment - Siwei Lin; Nan Chen (Earth Science Informatics, 2023)

Correction to: Automatic lithology identification method based on efficient deep convolutional network - Yan Guo; Zhuowu Li; Weihua Lin; Ji Zhou; Shixiang Feng; Luyu Zhang; Fujiang Liu (Earth Science Informatics, 2023)

Automatic lithology identification method based on efficient deep convolutional network - Yan Guo; Zhuowu Li; Weihua Lin; Ji Zhou; Shixiang Feng; Luyu Zhang; Fujiang Liu (Earth Science Informatics, 2023)

Keywords Query of uncertain spatiotemporal data based on XML - Changming Xu; Lin Zhu; Luyi Bai; Juan He (Earth Science Informatics, 2023)

Application of improved support vector machine in geochemical lithology identification - Shitao Yin; Xiaochun Lin; Yongjian Huang; Zhifeng Zhang; Xiang Li (Earth Science Informatics, 2023)

Spatiotemporal variability assessment and accuracy evaluation of Standardized Precipitation Index and Standardized Precipitation Evapotranspiration Index in Malaysia - Yi Xun Tan; Jing Lin Ng; Yuk Feng Huang (Earth Science Informatics, 2023)

Geochronology and structural deformation of Precambrian metamorphic basement in the eastern Jiangnan orogenic belt: constraints on the assembly time of the Yangtze and Cathaysia blocks - Yangyang Wang; Chuanzhong Song; Jiahao Li; Shoufa Lin; Zhenwei Li; Fang Yuan; Shenglian Ren (Earth Science Informatics, 2022)

OpenAltimetry - rapid analysis and visualization of Spaceborne altimeter data - Siri Jodha S. Khalsa; Adrian Borsa; Viswanath Nandigam; Minh Phan; Kai Lin; Christopher Crosby; Helen Fricker; Chaitan Baru; Luis Lopez (Earth Science Informatics, 2022)
NASA’s Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) carries a laser altimeter that fires 10,000 pulses per second towards Earth and records the travel time of individual photons to measure the elevation of the surface below. The volume of data produced by ICESat-2, nearly a TB per day, presents significant challenges for users wishing to efficiently explore the dataset. NASA’s National Snow and Ice Data Center (NSIDC) Distributed Active Archive Center (DAAC), which is responsible for archiving and distributing ICESat-2 data, provides search and subsetting services on mission data products, but providing interactive data discovery and visualization tools needed to assess data coverage and quality in a given area of interest is outside of NSIDC’s mandate. The OpenAltimetry project, a NASA-funded collaboration between NSIDC, UNAVCO and the University of California San Diego, has developed a web-based cyberinfrastructure platform that allows users to locate, visualize, and download ICESat-2 surface elevation data and photon clouds for any location on Earth, on demand. OpenAltimetry also provides access to elevations and waveforms for ICESat (the predecessor mission to ICESat-2). In addition, OpenAltimetry enables data access via APIs, opening opportunities for rapid access, experimentation, and computation via third party applications like Jupyter notebooks. OpenAltimetry emphasizes ease-of-use for new users and rapid access to entire altimetry datasets for experts and has been successful in meeting the needs of different user groups. In this paper we describe the principles that guided the design and development of the OpenAltimetry platform and provide a high-level overview of the cyberinfrastructure components of the system.

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

A general characterization of representing spatiotemporal data and determining topological relations based on OWL - Xiangfu Meng; Lin Zhu; Yan Wang; Xiaoyan Zhang (Earth Science Informatics, 2022)

Texture mapping of geological modeling based on parameterization - Lin Liu; Jianfeng He; Hongling Wang; Zhibo Wang (Earth Science Informatics, 2021)

Applicability evaluation and improvement of different snow evaporation calculation methods in the Great Xing’an mountains - Youwei Lin; Tijiu Cai; Cunyong Ju; Xueqing Cui (Earth Science Informatics, 2021)

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Street-block collapsed buildings assessment: A case study of Banqiao District, New Taipei City - ITien Lo; ChingYuan Lin; ChengTao Yang; YingJi Chuang; ChiHao Lin (Earth Science Informatics, 2021)

Anomalies in continuous GPS data as precursors of 15 large earthquakes in Western North America during 2007-2016 - Nan Li; Xiangzeng Kong; Ling Lin (Earth Science Informatics, 2020)

Three-dimensional Forest growth simulation in virtual geographic environments - Liyu Tang; Xianmin Peng; Chongcheng Chen; Hongyu Huang; Ding Lin (Earth Science Informatics, 2019)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Unmanned aerial vehicle based remote sensing method for monitoring a steep mountainous slope in the Three Gorges Reservoir, China - Haifeng Huang; Jingjing Long; Haiyu Lin; Lei Zhang; Wu Yi; Bangjun Lei (Earth Science Informatics, 2017)

An irregular triangle mesh buffer analysis method for boundary representation geological object in three-dimension - Nan Li; Leon Bagas; Mark Lindsay; Daniel Wedge; Lin Bai; Xianglong Song (Earth Science Informatics, 2017)

DEM generalization with profile simplification in four directions - Tianwu Ma; Yonggang Chen; You Hua; Zhende Chen; Xiaoyin Chen; Chengzhi Lin; Chunju Yang (Earth Science Informatics, 2017)

A new directional query method for polygon dataset in spatial database - Wei Hua Lin; Xiao Jun Tan; Fu Jiang Liu; Yan Yu; Wei Ming Wang (Earth Science Informatics, 2015)

Sobol’ sensitivity analysis of parameters in the common land model for simulation of water and energy fluxes - Jianhui Xu; Hong Shu; Hongnan Jiang; Lin Dong (Earth Science Informatics, 2012)